Prevention of postoperative pyelonephritis in patients after percutaneous nephrolithotripsy for large and coral kidney stones - Alexander I. Neymark; Dmitry V. Gryadunov; Egor V. Suzopov (ZAO "Consilium Medicum", 2023)
Background. Improving the results of prevention and treatment of postoperative pyelonephritis, the most frequent complication of percutaneous nephrolithotripsy, is an important task of modern urology. Aim. To determine the effectiveness of using physiotherapeutic procedures (magnetotherapy and laser therapy) for prevention of pyelonephritis development in the postoperative period. Materials and methods. The study included 72 patients with kidney stones of large size who underwent percutaneous nephrolithotripsy. The patients were divided into two groups: group 1 - 44 patients with kidney stone over 2.5 cm (including coral), group 2 - 28 patients with kidney stone over 2.5 cm (including coral) who underwent physiotherapeutic procedures in the perioperative period in combination with antibiotic therapy. All patients underwent percutaneous nephrolithotripsy with preoperative administration of antibacterial therapy. All patients underwent urine and stone culture, as well as laboratory and clinical evaluation of pyelonephritis attack development in the postoperative period. Results. Analysis of histories showed that in group 1, clinical symptoms of pyelonephritis exacerbation were observed more frequently in operated patients than in patients who underwent physical therapy in the perioperative period. The severity and duration of hyperthermia in the group 2 was noted to be not so high and prolonged. The percentage of microflora detection in urine and stone cultures was insignificantly different in both groups. At the same time, the level of leukocytosis in the group 2 in the postoperative period was on average lower, a 3-fold decrease in the frequency of prescribing "reserve" antibacterial drugs was also revealed. Conclusion. In patients with large and coral kidney stones physiotherapeutic procedures can be used in combination with antibacterial therapy for prevention and treatment of pyelonephritis exacerbation in the postoperative period after percutaneous nephrolithotripsy.